Assessing The Triple Bottom Line: a Cross-Sectional Analysis of Economic, Social, and Environmental Sustainability in Contemporary Development Projects - Saeed Angorani (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2025)
Purpose: The purpose of this research is to investigate the interrelationships between economic, social, and environmental components in modern development initiatives, as well as their implications for sustainability. The main goal is to decipher the complex dynamics and consequences of various variables in order to provide insights for holistic project planning and decision-making. Design/Methodology/Approach: A cross-sectional study was carried out utilising a questionnaire-based survey distributed to 500 participants in various development programmes. The study used statistical analyses such as Pearson correlation coefficients and t-tests to investigate the links between economic, social, and environmental variables, as well as their influence on social and environmental sustainability. Findings: The findings show substantial relationships between economic performance and favourable social and environmental indices, highlighting the interconnectivity of the two. Furthermore, a significant association was discovered between Economic, Social, and Environmental Indicators and the social impact on local communities and stakeholders. Originality/Value: This study adds new perspectives by objectively illustrating the interdependence of economic, social, and environmental factors in development programmes. The study emphasises the need of evaluating various variables concurrently for informed decision-making and long-term project results.